KONFLIK ANTARA KEPALA DESA DAN BADAN PERMUSYAWARATAN DESA - Zulkifli Zulkifli (MAHAKAM: Jurnal Ilmu-Ilmu Sosial, 2012)
This study tries to provide an overview of the conflict that often occurs at the village level, is expected to manage the village, the village head of the village along with BPD can work together to achieve the common goal of building the village together. In the implementation of the machinery of government in the village there are definite differences in the vision to see something happen, whether it comes to governance, village regulations, funding issues or other issues .. Conflicts that arise or occur between the village chief and BPD can also be triggered by aspects that have happened before as when the village head election